2011
DOI: 10.1016/b978-0-12-387690-4.00005-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of Circadian Timekeeping in Drosophila

Abstract: A genetic screen for mutants that alter circadian rhythms in Drosophila identified the first clock gene - the period (per) gene. The per gene is a central player within a transcriptional feedback loop that represents the core mechanism for keeping circadian time in Drosophila and other animals. The per feedback loop, or core loop, is interlocked with the Clock (Clk) feedback loop, but whether the Clk feedback loop contributes to circadian timekeeping is not known. A series of distinct molecular events are thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
388
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(403 citation statements)
references
References 180 publications
(358 reference statements)
9
388
0
6
Order By: Relevance
“…Broadly, circadian clocks comprise three main modules: (i) sensors that perceive the entrainment signals from the environment; (ii) molecular oscillators of transcriptionaltranslational feedback loops that maintain the clock pacing and transmit rhythmic signals to downstream components; and (iii) clock-controlled genes (CCGs) that coordinate circadian responses within cells (Harmer et al, 2001;Hardin, 2011;Reitzel et al, 2013;Takahashi, 2017). In animals, our understanding of the clock general circuitry largely draws from work on mammal and insect model species, which has revealed that the topology of the molecular oscillator is conserved across these divergent bilaterian lineages (Hardin, 2011;Takahashi, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadly, circadian clocks comprise three main modules: (i) sensors that perceive the entrainment signals from the environment; (ii) molecular oscillators of transcriptionaltranslational feedback loops that maintain the clock pacing and transmit rhythmic signals to downstream components; and (iii) clock-controlled genes (CCGs) that coordinate circadian responses within cells (Harmer et al, 2001;Hardin, 2011;Reitzel et al, 2013;Takahashi, 2017). In animals, our understanding of the clock general circuitry largely draws from work on mammal and insect model species, which has revealed that the topology of the molecular oscillator is conserved across these divergent bilaterian lineages (Hardin, 2011;Takahashi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In animals, our understanding of the clock general circuitry largely draws from work on mammal and insect model species, which has revealed that the topology of the molecular oscillator is conserved across these divergent bilaterian lineages (Hardin, 2011;Takahashi, 2017). Specifically, two interconnected regulatory loops are organized around a pair of basic helix-loop-helix-Per-ARNTSim (bHLH-PAS) transcription factors, Clock and Cycle (Bmal1), that activate the transcription of other clock elements.…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, a set of proteins (e.g. period, clock, cryptochrome) cycle as a result of negative feedback loops formed by the interactions of these proteins at the transcriptional and translational levels (Bell-Pedersen et al, 2005;Hardin, 2011). At the level of the organism, various pacemakers in the brain, as well as the periphery, work together to integrate multiple predictable changes of the environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Light signals are received through the blue-light photoreceptor CRYPTO-CHROME (dCRY), the expression of which is under clock control. dCRY associates with dTIM in a light-dependent manner and promotes its proteasome-mediated degradation (1). Cryptochromes are flavoproteins highly similar to photolyases, from which they have probably evolved, but across evolution they have lost or reduced the photolyase activity and gained roles in signaling (2).…”
mentioning
confidence: 99%